SEMICONTINUOUS SEPARATION OF DIMETHYL ETHER FROM BIOMASS - Pascall, Alicia A. (My University, 2013)
Environmental concerns about greenhouse gas emissions and energy security are the main drivers for the production of alternative fuels from bio-based feedstock. Dimethyl ether has attracted interest of many researches and is touted as “A fuel for the 21st century” due to its versatility. However, the production of DME from biomass is dependent on the overall economics of its production.
This thesis considers the application of semicontinuous distillation to improve the economics of the separation section in a biomass-to-DME facility. Semicontinuous distillation systems operate in a forced cycle to effect multiple separations using a single distillation column integrated with a middle vessel. The control system plays an integral role in the driving the forced cycle behaviour of the process in which no steady state exists.
The separation section consists of a series of flash drums followed by a distillation train consisting of three (3) columns. In the first phase of this work, a semicontinuous system was developed to achieve the separation of the second and third distillation columns in the separation section. Rigorous models were used to simulate the semicontinuous system in which several control configurations were evaluated. The final control structure based on classic PI control was shown to achieve the specification objectives of the system and handle disturbances while avoiding weeping and flooding conditions. Optimization followed by an economic analysis showed that the semicontinuous system was economically preferable to the traditional continuous process for a range of DME production rates.
Next, a semicontinuous system was developed to achieve the separation of the first and second distillation columns in the separation section. In this phase the application of semicontinuous distillation was extended to partial condenser configurations and the separation of biphasic mixtures. The control structure developed was effective in handling disturbance, attaining specification objectives while remaining with operational limits. An economic analysis, however, showed the traditional continuous configuration to be more economical for all DME production rates. Findings show that the operating cost is highly depending on the middle vessel purity so while uneconomical for this process it could result in favourable economics for less stringent purity specifications.
Keywords: Semicontinuous; Dimethyl Ether; Biomass; Process Control and Systems; Process Control and Systems